Monitoring Backbone Hydrogen‐Bond Formation in β‐Barrel Membrane Protein Folding. Issue 20 (9th April 2016) - Raschle, Thomas; Rios Flores, Perla; Opitz, Christian; Müller, Daniel J.; Hiller, Sebastian
Abstract: β‐barrel membrane proteins are key components of the outer membrane of bacteria, mitochondria and chloroplasts. Their three‐dimensional structure is defined by a network of backbone hydrogen bonds between adjacent β‐strands. Here, we employ hydrogen–deuterium (H/D) exchange in combination with NMR spectroscopy and mass spectrometry to monitor backbone hydrogen bond formation during folding of the outer membrane protein X (OmpX) from E. coli in detergent micelles. Residue‐specific kinetics of interstrand hydrogen‐bond formation were found to be uniform in the entire β‐barrel and synchronized to formation of the tertiary structure. OmpX folding thus propagates via a long‐lived conformational ensemble state in which all backbone amide protons exchange with the solvent and engage in hydrogen bonds only transiently. Stable formation of the entire OmpX hydrogen bond network occurs downhill of the rate‐limiting transition state and thus appears cooperative on the overall folding time scale. Abstract : Folding mechanisms of β‐barrel membrane proteins are not understood at the atomic level. H/D‐exchange was applied to monitor hydrogen‐bond formation during folding of the β‐barrel membrane protein OmpX at atomic resolution. Hydrogen bond formation kinetics are uniform in the entire barrel, indicating cooperative formation of the hydrogen bond network.